Lipid values ​​and postmenopausal women of childbearing age. - Guerrero, Paola (2015)
OBJECTIVES: To compare the lipid values in women of childbearing age (MEF) and postmenopausal (MPM). Design: Descriptive, prospective, transverse and observational study. MATERIALS AND METHODS: The universe was formed 97 494 women over 18 years living in the district of Piura, collected and calculated and shown by biphasic cluster sampling, was 253. age, weight, height, and FUR was evaluated. We analyzed fasted total cholesterol (TC), LDL cholesterol (LDL-C), HDL cholesterol (HDL-C) and triglyceride (TG), using the Trinder enzymatic method using Wiener lab reagents. Split the sample into two groups: women of childbearing age (MEF) and postmenopausal women (MPM). RESULTS: 54.2% (137) was MEF The MEF group had mean age 32.9 ± 8.3 years, while the MPM, 53.8 ± 8.2 years. TC> 240 mg% was found in 22 (16.1%) of the MEF Y43 (37.1%) of MPM was statistically significant (p <0.01). The values of c-HDL> 160 mg% and Tg> 200 mg% were in 19 (13.9%) and 9 (6%) of MEF, compared with 38 (32.8%) and 21 (18.1% ) MPM (p <0.01). HDL-C <45 mg% was found in 21 (15.3%) of MEF and 23 (19.8%) of MPM, not statistically significant (p> 0.05). CONCLUSIONS: We found that the CT, c-LDLy Tg increase significantly after menopause in women Piura, finding no difference in the values of HDL-C.